Integrated Industrial Estate Development Strategy in Increasing Competitiveness Through Technological Innovation and Research - Elli Sulistyaningsih; Sugeng Siswanto (MultiTech Publisher, 2023)
The unified and integrated industrial estate is an industrial development model that aims to create a superior business environment by integrating various industries and utilizing innovative technology and research. The integrated and integrated industrial area development strategy is very important to increase the competitiveness of companies and countries in today's highly competitive global market. Through the development of integrated industrial estates, companies can optimize resource potential and market access more effectively.The application of innovative technology and research is the key to increasing the competitiveness of companies and countries. In an integrated and integrated industrial area, companies can apply the latest and innovative production technologies that will speed up the production process, improve product quality and reduce production costs. In addition, the integrated industrial area also allows companies to collaborate in new research and development, thereby creating innovative and superior products for the global market.Increasing the competitiveness of integrated and integrated industrial areas is also supported by government support in the form of policies and regulations that accommodate industrial needs. Governments can provide incentives to industry to encourage innovative use of technology and research. In addition, the government can also facilitate the exchange of information between companies in integrated and integrated industrial zones, strengthen research and development collaborations, and facilitate the development of human resources in the fields of technology and research.